EVALUASI PELAKSANAAN PROGRAM ASESMEN NASIONAL BERBASIS KOMPUTER DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR (STUDI KASUS PADA UPT SD NEGERI 1 TANJUNG ANOM) - sigit ahmadi Putra; Juhri Abdul Muin; Muhammad Badrun; Fatqul Hajar Aswad (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study aims to evaluate the implementation of the Computer-Based National Assessment (ANBK) in improving the quality of education at the elementary school level. The research employed a qualitative approach with an evaluative design using the CIPP model (Context, Input, Process, Product). The study was conducted at SD Negeri 1 Tanjung Anom, Ambarawa District, Pringsewu Regency, Lampung Province, involving the school principal, teachers, proctors, and technicians as research participants. Data were collected through interviews, observations, and document analysis, and analyzed using qualitative techniques of data reduction, data display, and conclusion drawing.The findings indicate that the implementation of ANBK is aligned with national policies; however, the understanding of the program’s objectives remains largely administrative and has not been fully utilized as a strategic tool for quality improvement. In terms of input, the school has prepared supporting resources, yet limitations remain in human resource competencies and information technology infrastructure. The process dimension shows that ANBK was implemented according to established procedures, although its effectiveness was constrained by technical issues and students’ readiness. Regarding the product dimension, ANBK has produced comprehensive educational quality mapping data, but the use of assessment results for decision-making and instructional improvement has not been optimal. The study concludes that strengthening policy understanding, improving resource readiness, and systematically utilizing assessment results are essential for ANBK to function effectively as an instrument for sustainable quality improvement..